2013
DOI: 10.4103/2278-960x.118658
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of doppler velocimetry in pregnancy-induced hypertension in a rural population of a developing country

Abstract: Background: Pregnancy-induced hypertension (PIH) remains a great challenge to obstetricians. Doppler velocimetry can detect fetal compromise much before other antepartum tests. Aim: The aim of this study is to detect the changes of uterine artery, umbilical artery and middle cerebral artery in PIH by Doppler velocimetry. Subjects and Methods: This prospective study was conducted on hundred subjects with PIH. Doppler studies were carried, and parameters recorded in uterine, umbilical and middle cerebral artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Nhưng nhìn chung thì giá trị S/D có giá trị cao trong tiên lượng tiền sản giật. Kết quả nghiên cứu của chúng tôi tương đồng với nghiên cứu của tác giả Havra [11] nghiên cứu đoàn hệ tiến cứu trên 100 thai phụ, kết quả nghiên cứu cho thấy giá trị S/D trên siêu âm Doppler động mạch tử cung tiên lượng tiền sản giật có độ nhạy 60%, độ đặc hiệu 93,7%, giá trị tiên đoán dương 33,3%, giá trị tiên đoán âm 97,3%. Ở nghiên cứu này tác giả cũng loại trừ các trường hợp tăng huyết áp mãn và không có can thiệp điều trị dự phòng tiền sản giật như trong nghiên cứu của chúng tôi.…”
Section: Giá Trị Của Chỉ Số S/d Trên Siêu âM Doppler độNg Mạch Tử Cun...unclassified
“…Nhưng nhìn chung thì giá trị S/D có giá trị cao trong tiên lượng tiền sản giật. Kết quả nghiên cứu của chúng tôi tương đồng với nghiên cứu của tác giả Havra [11] nghiên cứu đoàn hệ tiến cứu trên 100 thai phụ, kết quả nghiên cứu cho thấy giá trị S/D trên siêu âm Doppler động mạch tử cung tiên lượng tiền sản giật có độ nhạy 60%, độ đặc hiệu 93,7%, giá trị tiên đoán dương 33,3%, giá trị tiên đoán âm 97,3%. Ở nghiên cứu này tác giả cũng loại trừ các trường hợp tăng huyết áp mãn và không có can thiệp điều trị dự phòng tiền sản giật như trong nghiên cứu của chúng tôi.…”
Section: Giá Trị Của Chỉ Số S/d Trên Siêu âM Doppler độNg Mạch Tử Cun...unclassified
“…Worldwide, Preeclampsia complicates about 5-10% of all pregnancies. It is one of the leading causes of maternal and perinatal mortality, fetal growth restriction and prematurity [1][2][3][4][5][6][7][8][9] . According to World Health Organization (WHO), Preeclampsia is about seven times higher in developing countries [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Identifying at-risk fetuses in developing countries where the perinatal mortality rate is about 14 times higher than in developed countries is vital to improving perinatal outcomes [5] . Some studies have found that haemodynamic indices of the fetal umbilical artery (UmA) and Middle cerebral artery (MCA) may detect fetal compromise much before any other antepartum test [6,7] .…”
Section: Introductionmentioning
confidence: 99%